Życie Przed Tobą . A Life to Live - Adamek, Maciej (Poland, 2003)
Verzio FF Start: 01:25:00, End: 01:46:00 Can we see the world of the blind? This film is a perceptive portrayal of blind children, for whom touch, sound, smell, and taste comprise a plentiful universe. Playing, dreaming, talking about their future, the children who cannot see with their eyes learn to sharpen their senses. They face many challenges in a world that is hostile to people who are not like us, the viewers. Using images to tell the stories of hearing, smelling, touching, the film shows how the perception-gap can be bridged with love and care.